Factors Associated with Pediatric Dentists' Choice of Amalgam: Choice-Based Conjoint Analysis Approach. (July 2019) - Bakhurji, E.; Scott, T.; Sohn, W.
Background: The Minamata treaty (2013) enacted a globally binding agreement to phase down amalgam use, which may significantly affect dental care for underserved populations. To comply with the Minamata treaty, strategic approaches need to be implemented to reduce amalgam use while imposing minimal risk on the dental care of the underserved. Objectives: To establish strategic approaches to reduce amalgam use, the aim of this study is to use a marketing research analysis to determine which patient-related factors influence pediatric dentists' choice of amalgam. Methods: A survey containing questions regarding amalgam use, perception about the environmental impact of amalgam waste, and hypothetical clinical scenarios of a child with dental caries with varying levels of caries risk and types of dental insurance was developed and pretested. Emails linked to an electronic survey were sent via Qualtrics to all active American Academy of Pediatric Dentistry members ( n = 5, 101), followed by 3 reminders. Descriptive analysis and choice-based conjoint analysis were performed to investigate trade-offs between selected factors, using SAS version 9.3. Results: Of 892 (17.6%) replies, 850 responses were eligible for analysis. Only 385 (45%) respondents indicated using amalgam, and their responses were analyzed in the conjoint model. Respondents' selection of amalgam varied between 8% and 28% across all the clinical scenarios, with most respondents choosing composite or stainless steel crowns. Conjoint analysis revealed that, while both caries risk and type of insurance affected respondents' decision about amalgam use, caries risk was the driving factor in decision-making for using amalgam. Conclusion: These results underscore the importance of prevention and management of risk factors to successfully phase down amalgam use. Knowledge Transfer Statement: Our study applied the marketing research tool, choice-based conjoint analysis, to investigate the relative importance of different factors on dentists' decision-making regarding amalgam use. This study should be of great interest to policy makers when developing strategic approaches to comply with the 2013 United Nations Environment Programme (a.k.a. Minamata treaty) policy recommendations for phase-down of dental amalgam.